To solve the system of equations by elimination, we can subtract the second equation from the first equation.
(7x - 8y) - (7x - 4y) = -3 - (-19)
Simplifying, we have:
-8y + 4y = -3 + 19
-4y = 16
Dividing both sides by -4, we get:
y = -4
Now, we can substitute this value of y back into one of the original equations to solve for x. Let's substitute it into the first equation:
7x - 8(-4) = -3
Simplifying, we have:
7x + 32 = -3
Subtracting 32 from both sides, we get:
7x = -35
Dividing both sides by 7, we have:
x = -5
Therefore, the solution to the system of equations is x = -5 and y = -4.
solve by useing elimination7x − 8y = –3 7x − 4y = –19
1 answer